Comparison and validation of screening tools for substance use in pregnancy: a cross-sectional study conducted in Maryland prenatal clinics. Issue 2 (17th February 2018) - Coleman-Cowger, Victoria H; Oga, Emmanuel A; Peters, Erica N; Trocin, Kathleen; Koszowski, Bartosz; Mark, Katrina
Abstract : Introduction: Prescription-drug use in the USA has increased by more than 60% in the last three decades. Prevalence of prescription-drug use among pregnant women is currently estimated around 50%. Prevalence of illicit drug use in the USA is 14.6% among pregnant adolescents, 8.6% among pregnant young adults and 3.2% among pregnant adults. The first step in identifying problematic drug use during pregnancy is screening; however, no specific substance-use screener has been universally recommended for use with pregnant women to identify illicit or prescription-drug use. This study compares and validates three existing substance-use screeners for pregnancy—4 P's Plus, National Institute on Drug Abuse (NIDA) Quick Screen/Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) and the Substance Use Risk Profile-Pregnancy (SURP-P) scale. Methods and analysis: This is a cross-sectional study designed to evaluate the sensitivity, specificity and usability of existing substance-use screeners. Recruitment occurs at two obstetrics clinics in Baltimore, Maryland, USA. We are recruiting 500 participants to complete a demographic questionnaire, NIDA Quick Screen/ASSIST, 4 P's Plus and SURP-P (ordered randomly) during their regularly scheduled prenatal appointment, then again 1 week later by telephone. Participants consent to multidrug urine testing, hair drug testing and allowing access to prescription drug and birth outcome data from electronic medical records. For each screener, reliability and validity will be assessed. Test–retest reliability analysis will be conducted by examining the results of repeated screener administrations within 1 week of original screener administrations for consistency via correlation analysis. Furthermore, we will assess if there are differences in the validity of each screener by age, race and trimester. Ethics and dissemination: This study is approved by the Institutional Review Board of the University of Maryland (HP-00072042), Baltimore, and Battelle Memorial Institute (0619–100106433). All participants are required to give their informed consent prior to any study procedure.